ANALISIS KUALITAS LAYANAN WEBSITE GRAB MENGGUNAKAN METODE WEBQUAL DI AREA KOTA DENPASAR BALI - Putri Anggreni; I Made Wahyu Artha Wikrama (UNHI Press, 2018)
Making a website so far only focused on the system, the look and content of the website content is presented regardless of the website user satisfaction, this study aims to determine the level of user satisfaction grab website. WebQual research method using 4.0 as well as the scale linkert as the study interval. WebQual is one method or technique of measuring the quality of a website based on the perception of the end user. 4.0 WebQual method is based on three dimensions of usability, information quality dimensions and dimensional quality of the interaction. In the analysis process used tranches sample of respondents to 120 people from among the people who use the website grab. The study used a questionnaire directly in tertuls verbally and directly collected and processed data. The next stage is the analysis of data consisting of validity, reliability and judgment with linkert scale. On the validity of the test using the formula Pearson Bevariate while reliability test using Cronbach's alpha formula. In the assessment using the scale linkert with 4 scale interval. Based on the research results obtained have an average total satisfaction very high value on the quality of the website grab the results in each of these dimensions WebQual method wherein the usability dimension produces an average score of 3.34, the dimensions of information quality and interaction quality 3,58 3, 45, in other words in the Likert scale interva include very satisfied. This study is useful as information as information to the grab to improve the quality of website services on an ongoing basis to improve user satisfaction grab website.